2004
DOI: 10.1557/proc-824-cc5.7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavior of R7T7-type nuclear glass: Current state of knowledge and outlook

Abstract: This article reviews current knowledge of the long-term behavior of R7T7-type glass during the thermal phase and in geological repository conditions (aqueous alteration). In interim storage R7T7 glass can be considered to conserve its integrity over time. In geological repository conditions, the mechanisms of glass alteration by water have been identified and parameter values have been assigned to the reaction kinetics for wide variations of the influential factors (temperature, pH, flow rate, S/V ratio, etc.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…The results of the investigations agree with the existing data on the meaning of embryos of the surface layer and the intermediate gel-like layer, which, possessing sorption properties, impede further leaching of the radionuclides out of the glass blocks [3,4,[6][7][8][9]17].…”
supporting
confidence: 87%
“…The results of the investigations agree with the existing data on the meaning of embryos of the surface layer and the intermediate gel-like layer, which, possessing sorption properties, impede further leaching of the radionuclides out of the glass blocks [3,4,[6][7][8][9]17].…”
supporting
confidence: 87%
“…According to the most documented theory on glass corrosion, two coupled mechanisms control the residual alteration rate of nuclear glass: (1) interdiffusion, involving water transport from solution to the pristine glass and diffusion through the alteration film of species arising from glass dissolution; (2) precipitation of silicate phases, generally crystalline (Abrajano et al, 1990;Gin and Mestre, 2001;Gin et al, 2004Gin et al, , 2011Gin et al, , 2012Curti et al, 2006;Frugier et al, 2006Frugier et al, , 2008Valle et al, 2010). Recent studies have shown that the transport of aqueous species within the alteration film can be affected by pore closure in the gel Cailleteau et al, 2008), and/or by silica saturation of the pore solution in the interdiffusion zone (Maeda et al, 2012;Gin et al, 2013b,c).…”
Section: Discussionmentioning
confidence: 99%
“…Cation interdiffusion is often considered as a short duration tertiary process in the general process of glass corrosion [52,66]. However since the first experimental studies it has been clear that the time of change from the first (diffusion-controlled) mechanism to the second (hydrolysis) depends upon the temperature and composition of glass [16,17].…”
Section: Discussionmentioning
confidence: 99%